KARAKTERISTIK DAN HAKIKAT FATWA DSN MUI NOMOR. 54/DSN-MUI/X/2006 TENTANG SYARIAH CARD SEBAGAI SOLUSI KREDIT BERMASALAH - Hida, Ziyana Nur (Fakultas Syariah (Syari'ah Faculty ), 2024)
This article discusses the characteristics and nature of the fatwa of Sharia Economic Law in depth by discussing the solution to bad credit issued by the DSN-MUI. The need of the Muslim community for legal equivalence in economic transactions has led the Indonesian Ulema Council to formulate a special institution to jointly sharia the economy of the community and socialise the Islamic economy. This is proof that the conventional economy cannot fulfil the expectations of Muslims to be able to practice sharia in a kaffah manner in various aspects of life. The establishment of the National Sharia Council (DSN) as a special institution that focuses on issuing fatwas on Islamic economic law is a motivation for Muslims in transactions, fatwas based on the Qur'an sunnah and ijtihad of scholars are milestones that distinguish Islamic economic transactions and conventional economics. The role of world scholars in seeing the rules of a country is a scientific contribution, especially from the fatwa issued as a solution to bad credit. The majority of scholars oppose the fatwa because it is considered no different from usury jahiliyah. This research uses a descriptive analysis approach sourced from literature studies.